Detection, isolation and characterization of 8-hydroxycarbostyril and 8-hydroxy-3, 4-dihydrocarbostyril : two novel urinary metabolites of microbial origin in rats - Leng, H. M. J (Stellenbosch : Stellenbosch University, 2012)
One copy microfiche.